Investigating the ROS Formation and Particle Behavior of Food-Grade Titanium Dioxide (E171) in the TIM-1 Dynamic Gastrointestinal Digestion Model - Nicolaj S. Bischoff; Anna K. Undas; Greet van Bemmel; Jacco J. Briedé; Simone G. van Breda; Jessica Verhoeven; Sanne Verbruggen; Koen Venema; Dick T. H. M. Sijm; Theo M. de Kok (Nanomaterials)
Food-grade titanium dioxide (E171) is widely used in food, feed, and pharmaceuticals for its opacifying and coloring properties. This study investigates the formation of reactive oxygen species (ROS) and the aggregation behavior of E171 using the TNO Gastrointestinal (GI) model, which simulates the stomach and small intestine. E171 was characterized using multiple techniques, including electron spin resonance spectroscopy, single-particle inductively coupled plasma–mass spectrometry, transmission electron microscopy, and dynamic light scattering. In an aqueous dispersion (E171-aq), E171 displayed a median particle size of 79 nm, with 73–75% of particles in the nano-size range (<100 nm), and significantly increased ROS production at concentrations of 0.22 and 20 mg/mL. In contrast, when E171 was mixed with yogurt (E171-yog), the particle size increased to 330 nm, with only 20% of nanoparticles, and ROS production was inhibited entirely. After GI digestion, the size of dE171-aq increased to 330 nm, while dE171-yog decreased to 290 nm, with both conditions showing a strongly reduced nanoparticle fraction. ROS formation was inhibited post-digestion in this cell-free environment, likely due to increased particle aggregation and protein corona formation. These findings highlight the innate potential of E171 to induce ROS and the need to consider GI digestion and food matrices in the hazard identification/characterization and risk assessment of E171.